The Absence of Caspase-8 in the Dopaminergic System Leads to Mild Autism-like Behavior - Suárez-Pereira, I.; García-Domínguez, I.; Bravo, L.; Santiago, M.; García-Revilla, J.; Espinosa-Oliva, A. M.; Alonso-Bellido, I. M.; López-Martín, C.; Pérez-Villegas, E. M.; Armengol, J. A.; Berrocoso, E.; Venero, J. L.; et al. (Frontiers in Cell and Developmental Biology, 2022)
In the last decade, new non-apoptotic roles have been ascribed to apoptotic caspases. This family of proteins plays an important role in the sculpting of the brain in the early stages of development by eliminating excessive and nonfunctional synapses and extra cells. Consequently, impairments in this process can underlie many neurological and mental illnesses. This view is particularly relevant to dopamine because it plays a pleiotropic role in motor control, motivation, and reward processing. In this study, we analyze the effects of the elimination of caspase-8 (CASP8) on the development of catecholaminergic neurons using neurochemical, ultrastructural, and behavioral tests. To do this, we selectively delete the CASP8 gene in cells that express tyrosine hydroxylase with the help of recombination through the Cre-loxP system. Our results show that the number of dopaminergic neurons increases in the substantia nigra. In the striatum, the basal extracellular level of dopamine and potassium-evoked dopamine release decreased significantly in mice lacking CASP8, clearly showing the low dopamine functioning in tissues innervated by this neurotransmitter. This view is supported by electron microscopy analysis of striatal synapses. Interestingly, behavioral analysis demonstrates that mice lacking CASP8 show changes reminiscent of autism spectrum disorders (ASD). Our research reactivates the possible role of dopamine transmission in the pathogenesis of ASD and provides a mild model of autism.